Michael Jackson : A Celebration - Roberts, Chris (London Sevenoaks, 2009)
"Preposterously talented, fronting the Jackson 5 from early childhood, he captivated kids, and more than a few grown-ups, with fancy footwork, effortless high C's and charisma to burn. launched Jackson into a new level of celebrity stratosphere - more media, more attention, more intensity - that even Elvis or the Beatles had never experienced. How he dealt with that fame - how he used it, and how it, arguably, overwhelmed him - became, in later years, the heart of the Michael Jackson story."--Publisher description.
Include Illustration
Keywords: Rock musicians -- United States -- Jackson, Michael, 1958-2009